COMPREHENSIVE EVALUATION OF COMPLETE DENTURE CLEANSING AND MAINTENANCE HABITS AMONG ELDERLY PATIENTS- A CROSS SECTIONAL STUDY - Dhal, Angurbala; Garhnayak, Lokanath; Garhnayak, Mirna; Dev, Shruti; Hota, Sadananda; Kar, Aswini Kumar (International Journal of Psychosocial Rehabilitation, 2020)
Aim: This cross sectional study was performed to evaluate the complete denture cleansing and maintenance habits among elderly institutionalized patients. Materials & Methods: The present study was conducted in the department of Prosthodontics. This cross sectional study included 100 complete denture patients who have been delivered complete dentures in the recent past. Patients were screened, examined and finalized from the normal OPD of the department. A questionnaire was prepared which was having 10 questions about cleansing methodologies, cleaning frequencies, denture cleaning materials and other associated factors. Each patient was provided 10 questions via questionnaire. They are requested to truthfully respond. The relative importance of the study was explained to the patients. Results: out of 100 patients, males were 64 and females were 36. Total 30 patients were reported to age group >65 years. Just 6 patients were falling in the age range of 45-50 years. Therefore we can presume that most of the denture wearers were related to geriatric age groups. P value was reported to be significant for the age group of 45-50 . Conclusion: In the studied patients, researchers concluded that the overall status of complete denture hygiene and maintenance was below moderate level.